2017
DOI: 10.1209/0295-5075/117/68001
|View full text |Cite
|
Sign up to set email alerts
|

Time scales and species coexistence in chaotic flows

Abstract: Empirical observations in marine ecosystems have suggested a balance of biological and advection time scales as a possible explanation of species coexistence. To characterise this scenario, we measure the time to fixation in neutrally evolving populations in chaotic flows. Contrary to intuition the variation of time scales does not interpolate straightforwardly between the no-flow and well-mixed limits; instead we find that fixation is the slowest at intermediate Damköhler numbers, indicating long-lasting coex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(92 reference statements)
1
6
0
Order By: Relevance
“…In-line with the literature we will describe this by the so-called Damköhler number, Da (see e.g. 30 33 ); in the context of our model, the Damköhler number characterises the ratio of the time scales of the flow and the evolutionary process. In our simulations, one evolutionary event occurs every 1/( NDa ) time units.…”
Section: Results and Methodsmentioning
confidence: 79%
“…In-line with the literature we will describe this by the so-called Damköhler number, Da (see e.g. 30 33 ); in the context of our model, the Damköhler number characterises the ratio of the time scales of the flow and the evolutionary process. In our simulations, one evolutionary event occurs every 1/( NDa ) time units.…”
Section: Results and Methodsmentioning
confidence: 79%
“…We also anticipate that the results of this letter may inspire interesting investigations beyond the realms of political campaigning, for example to biological competition [33]. Indeed, there are clear parallels between this work and that of [7], who demonstrated that faster diffusing individuals dominate in spatial models of biological competition, and [34] who examine the evolutionary dynamics of mobile agents in chaotic flows. The underlying competition dynamics and mechanisms of establishing dominance are, however, entirely different.…”
mentioning
confidence: 66%
“…In-line with the literature we will characterise this by the so-called Damköhler number, Da (see e.g. [27][28][29][30] ). In our simulations, one evolutionary event occurs every 1/(N Da) time units.…”
Section: Models Of Stirred Populationsmentioning
confidence: 86%

Fast flowing populations are not well mixed

Herrerías-Azcué,
Pérez-Muñuzuri,
Galla
2017
Preprint
Self Cite